Factors controlling the relative abundances of anaerobic conditions in upland soils - Koenigsberger, Stephan (Kansas State University, 2020)
Anaerobic microenvironments, or microsites, are important regulators of C cycling in upland soils, but environmental factors that control their abundance are not well known. To help fill this knowledge gap, we examined variation in the redox state of upland soils at seven locations across the Kansas precipitation gradient. At each location, we used a Gidding’s probe to collect samples from three depth intervals (0-5, 5-15, and 15-30cm) at three land use types (native prairie, restored prairie, and agricultural). We measured 0.5 M HCl extractable Fe(II) and Fe(III), total organic carbon (TOC), pH, and particle size distribution, and used Fe(II) as our measure of the abundance of anaerobic microsites. We assessed the statistical significance of relationships between our parameters using Spearman’s rank correlation tests (p<0.05). Results show that Fe(II) content was positively correlated with TOC overall (r=0.52, p=2.99E-7), consistent with greater TOC storage in soils with more abundant anaerobic microsites. Fe(II) (r=0.51, p=4,849E-7)) and TOC (r=0.25, p=0.019) were both positively correlated with average annual precipitation. Increasing precipitation has the potential to increase anaerobic microsite abundance through two mechanisms: by decreasing O₂ transport within soil and by increasing organic C inputs. A positive correlation of clay abundance and Fe(II)(r=0.31, p=0.003) but not TOC in our dataset is consistent with the former mechanism. However, it is possible that both mechanisms contribute. Analysis of our results by land-use category shows that relationship between Fe(II) and TOC and their relationships with precipitation were significant for samples from agricultural and restored prairie fields but not native prairie fields. Taken together, these findings provide evidence that precipitation and land use influence soil redox and its relationship to carbon storage in upland soils. We believe that our results show the need for more studies to examine the relationships between soil redox parameters, TOC, and precipitation data at different time scales to aid in refining soil carbon models.
Keywords: Redox; Climate change; Precipitation; Carbon; Anaerobic; Iron